Publicación en revistas científicas por docentes de la Facultad de Estomatología de la Universidad Peruana Cayetano Heredia, 2010-2019 - Alvarez Sotelo, Silvana Katherine (2020)
Background: After the increase in scientific production in recent years, there aren't reports of the profile of the publications made by the professors at the Faculty of Stomatology in Universidad Peruana Cayetano Heredia in the last 10 years. Objective: Analyze the publications in scientific journals by professors at the Faculty of Stomatology in Universidad Peruana in the period 2010-2019. Materials and methods: The research was descriptive, observational, cross-sectional and retrospective, the scientific publications made by professors from 2010-2019 were identified. The variables were gender, professional practice, academic department, employment status, teaching category, academic degree, second specialty, publications by professors, type of publication, year of publication, internationally indexed, Scimago classification and WoS classification. The databases for the bibliographic search were Scielo, Pubmed, Google Scholar, Scopus and WoS. Results: It was evidenced that 58.38% (n = 101) of the teachers had at least one publication, in addition 52.28% (n = 241) of these publications were original articles, and in turn only 4.56% (n = 21) were classified Of the latter, according to SCIMAGO, it was found that 76.19% (n = 16) had FI <2 and 17 had a WoS classification where 47.06% (n = 8) belong to Q1. Conclusion: Most professors at the Faculty of Stomatology in the Universidad Peruana Cayetano Heredia have at least one publication in scientific journals in the period 2010-2019.